Medicinal and aromatic plants making healthy and wealthy - Kumar, Jitendra; Basak, B B; R, Nagaraja Reddy; Jat, R S (Indian Horticulture, 2019)
The medicinal and aromatic plants (MAPs) provide vast opportunity to strengthen health, food, nutrition, and livelihood security to farm families and ecological services to the environment. Their potential is especially immense in the Indian context where traditional systems of medicine have been used over the years to address human, animal and plant health. Globally, the potential is being recognized and it is becoming increasingly apparent that health for all can be assured only by strengthening traditional systems of medicine. Commercial importances of MAPs in recent years are expanding due to diversified usages of herbals in pharmaceutical, nutraceutical, cosmetic and agro-chemical industries. India’s existing contribution to the present global herbal trade is meager, valuating at US 150 million annually. The Indian Herbal Export Trade Registered about 137% growth from `554 crore (2005-06) to `1,318 crore (2010-11). Of the global trade of 7,592 million in 2011, the share of China and India was around 1,329 million and 790 million, respectively. Besides this, India is the second largest exporter of raw medicinal plant material, next to China and its domestic market for medicinal plants being `14,000 crore.